FOLFOX plus panitumumab or FOLFOX alone as additive therapy following R0/1 resection of RAS wild-type colorectal cancer liver metastases – The PARLIM trial (AIO KRK 0314). (September 2022) - Modest, Dominik Paul; Karthaus, Meinolf; Kasper, Stefan; Moosmann, Nicolas; Keitel, Verena; Kiani, Alexander; Uhlig, Jens; Jacobasch, Lutz; Fischer v. Weikersthal, Ludwig; Fuchs, Martin; Kaiser, Florian; Lerchenmüller, Christian; et al.
Abstract: Purpose: This trial investigates the addition of panitumumab to chemotherapy with fluorouracil/folinic acid and oxaliplatin (FOLFOX) in a 2:1 randomised, controlled, open-label, phase II trial in RAS wild-type colorectal cancer patients with R0/1-resected liver metastases. Experimental design: The primary endpoint was progression-free survival (PFS) two years after randomisation. The experimental arm (12 weeks of biweekly mFOLFOX6 plus panitumumab followed by 12 weeks of panitumumab alone) was considered active if the two-year PFS rate was ≥65%. Based on historical data, a two-year PFS rate of 50% was estimated in the control arm (12 weeks of biweekly FOLFOX). The trial was performed with a power of 80% and an alpha of 0.05. Secondary endpoints included overall survival (OS) and toxicity. The trial is registered with ClinicalTrials.gov, NCT01384994. Results: The full analysis set consists of 70 patients (pts) in the experimental arm and 36 pts in the control arm. The primary endpoint was missed with a two-year PFS of 35.7% with FOLFOX plus panitumumab and 30.6% in the control arm. In comparative analyses, trends towards improved PFS (HR 0.83; 95%CI, 0.52–1.33; P = 0.44) and OS (HR 0.70; 95% CI, 0.34–1.46; P = 0.34) were observed in favour of the panitumumab-based study arm. No new or unexpected safety signals were observed with FOLFOX plus panitumumab following liver resection. Conclusion: The PARLIM trial failed to demonstrate a two-year PFS rate of 65% after resection of colorectal liver metastases. The positive trends in survival endpoints may support future trials evaluating treatment with anti-EGFR agents after resection of liver metastases. Highlights: FOLFOX plus panitumumab after the resection of liver metastases is safe and feasible. The free-of-disease endpoint was missed with panitumumab and FOLFOX. Survival trends may suggest panitumumab efficacy after the resection of metastases.